Analysis Of The Influence Of Customer Satisfaction, Customer Value And Service Quality On Customer Loyalty Of State-Owned Bank In Indonesia - Zunan Setiawan; Donny Dharmawan; Loso Judijanto; Ita Nurcholifah; Suryani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study set out to examine how customer value and service quality affect customer satisfaction and how that affects customer loyalty. Purposive sampling is used in this study to choose 100 respondents who are bank clients who establish accounts in the regional offices in some big cities in Indoensia with a minimum account opening age of one year. The path analysis approach and the Sobel test are used in this study to assess the impact of intervening factors. The results of this study show that while customer value influences both customer happiness and loyalty, service quality only has an impact on customer satisfaction and does not affect customer loyalty. The results indicate that, in terms of indirect impacts, customer value has no influence on customer loyalty through customer satisfaction, and service quality has no effect on customer loyalty through customer satisfaction